PENGARUH BRAND AWARENESS TERHADAP KEPUTUSAN PEMBELIAN : Survei terhadap konsumen Khalistama Tour and Travel di Kota Bandung - Givari Mugiyadi, - (2018)
Travel agents Industry have a tight competition in offers with prices and best facilities to consumers. Various destination tourist destinations and various price offered by travel agents in big cities, including one of them is in Bandung city, as Khalistama tour and travel. In order to protect business, so Khalistama tour must have brand awareness good in the eyes of public research aims to understand the influence of brand awareness of the decision the purchase of consumers Khalistama tour and travel. Based on variable, so the kind of research used is research descriptive and verification. Technique data collection use primary data that is the questionnaire and also interview. While technique analysis the data used was regression analysis simple and also descriptive analysis. Population in this study is all of consumers who ever used services and the product of Khalistama tour, while the sample collection to research this is by using a technique sampling incidental to 200 people consumers of Khalistama tour and travel. The research results show that overall brand awareness owned by consumers or public has not been established well, but even so decision of purchase good enough are still need to optimized again in the future. Then brand awareness having influence a positive and significant of the purchase of decisions, as for the size of the influence brand awareness of the decision the purchase namely 62.7 % so inconclusive when brand public awareness to Khalistama better, the more higher the decision consumers to buy in Khalistama tour and travel.